Save the planet or close your eyes? Testing strategic ignorance in a charity context - Jo Thori Lind; Karine Nyborg; Anna Pauls (University of Oslo, Department of Economics, 2018)
Our lab experiment tests for strategic ignorance about the environmental consequences of one's actions. In a binary dictator situation based on the design by Dana, Weber, and Kuang (2007), we test whether the option to remain ignorant about the receiver's payoffs reduces generosity. Our receiver is a charity that engages in carbon offset. Contrary to previous findings by Dana, Weber, and Kuang (2007) and replications, the option to remain ignorant does not decrease generosity. Only 22% of dictators choose ignorance. We test social interaction by allowing another subject to force the dictator to learn the receiver's payoff, and by allowing the dictator to sanction that subject. When information can be imposed by another subject, almost all dictators choose information themselves, but this does not increase generosity. The possibility of sanctions does not discourage subjects from providing information to dictators.
Keywords: C92; D63; Q50; 330; Strategic ignorance; dictator game; experiment; social sanctions; carbon offset